Effects of partial selfing on the equilibrium genetic variance, mutation load, and inbreeding depression under stabilizing selection. (1st April 2018) - Abu Awad, Diala; Roze, Denis
Abstract: The mating system of a species is expected to have important effects on its genetic diversity. In this article, we explore the effects of partial selfing on the equilibrium genetic variance V g, mutation load L, and inbreeding depression δ under stabilizing selection acting on a arbitrary number n of quantitative traits coded by biallelic loci with additive effects. When the U / n ratio is low (where U is the total haploid mutation rate on selected traits) and effective recombination rates are sufficiently high, genetic associations between loci are negligible and the genetic variance, mutation load, and inbreeding depression are well predicted by approximations based on single‐locus models. For higher values of U / n and/or lower effective recombination, moderate genetic associations generated by epistasis tend to increase V g, L, and δ, this regime being well predicted by approximations including the effects of pairwise associations between loci. For yet higher values of U / n and/or lower effective recombination, a different regime is reached under which the maintenance of coadapted gene complexes reduces V g, L, and δ. Simulations indicate that the values of V g, L, and δ are little affected by assumptions regarding the number of possible alleles per locus.